A review of the physics of ice surface friction and the development of ice skating - Formenti, F. (Research in Sports Medicine, 2014)
Our walking and running movement patterns require friction between shoes and ground. The surface of ice is characterised by low friction in several naturally occurring conditions, and compromises our typical locomotion pattern. Ice skates take advantage of this slippery nature of ice; the first ice skates were made more than 4000 years ago, and afforded the development of a very efficient form of human locomotion. This review presents an overview of the physics of ice surface friction, and discusses the most relevant factors that can influence ice skates` dynamic friction coefficient. It also presents the main stages in the development of ice skating, describes the associated implications for exercise physiology, and shows the extent to which ice skating performance improved through history. This article illustrates how technical and materials` development, together with empirical understanding of muscle biomechanics and energetics, led to one of the fastest forms of human powered locomotion.